2003
DOI: 10.1002/jbm.b.10560
|View full text |Cite
|
Sign up to set email alerts
|

SEM and TEM analysis of water degradation of human dentinal collagen

Abstract: Recently several long-term studies have reported evidence of the hydrolytic degradation of collagen fibrils based on fractured surface observations after bond testing. Those studies suggested that one cause of the decline in the bond strength was the degradation of the collagen fibrils within the bonds. However, one concern has been raised that the dentinal collagen fibrils may be stable in water that does not contain oral bacteria or enzymes. Therefore, the present study aimed to clarify the micromorphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
0
29

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(169 citation statements)
references
References 17 publications
4
128
0
29
Order By: Relevance
“…40,42 Morphological studies indicate that the resin and collagen matrix may suffer degradation from storage. [48][49] Even though enamel adhesion is considered more safe and stable than dentin, 50 the current study showed failure regarding marginal sealing for enamel margins and in nearly all experimental conditions, which means that water caused damage in enamel margins as well as in dentin.…”
Section: Discussionmentioning
confidence: 56%
“…40,42 Morphological studies indicate that the resin and collagen matrix may suffer degradation from storage. [48][49] Even though enamel adhesion is considered more safe and stable than dentin, 50 the current study showed failure regarding marginal sealing for enamel margins and in nearly all experimental conditions, which means that water caused damage in enamel margins as well as in dentin.…”
Section: Discussionmentioning
confidence: 56%
“…Ideally, after acid-etching, the adhesive should completely infiltrate the delicate fibrillar network. Optimal resin infiltration is crucial to maximize bond strength [5,6] and bond durability [1], as unprotected collagen fibrils may be hydrolyzed over time [11,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of incompletely infiltrated collagen fibrils within the hybrid layers and additional entrapped water within the polymerized adhesives may expedite the degradation of resin-dentin bonds, resulting in clinical and visibly detectable microleakage [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A successful long-term dentin-resin bond depends on the formation of a homogenous and strong hybrid layer created by the perfect infiltration of resin monomers into dentin substrate (Nakabayashi et al, 1982). Morphological evidence of hydrolytic degradation of collagen in hybrid layers after an extended period has been presented in several studies (Sano et al, 1999;Hashimoto et al, 2000;Hashimoto et al, 2002;Hashimoto et al, 2003b;Hashimoto et al, 2003c). Degradation of collagen fibrils in the hybrid layer suggests the presence of exposed collagen fibrils.…”
Section: Release and Activation Of Mmps And Their Potential Roles In mentioning
confidence: 98%
“…For example: the application of simplified adhesives, insufficient resin infiltration (Hashimoto et al, 2000;Hashimoto et al, 2002;Hashimoto et al, 2003b;Hashimoto et al, 2003c;Tay and Pashley, 2003), sub-optimal polymerization (Eick et al, 1997;Cadenaro et al, 2005;Cadenaro et al, 2006), degradation of resin components (Hashimoto et al, 2000;De Munck et al, 2005;Tay and Pashley, 2003), high permeability of the bonded interface and activation of endogenous collagenolytic enzymes.…”
Section: Release and Activation Of Mmps And Their Potential Roles In mentioning
confidence: 99%